The live attenuated varicella-zoster virus vaccine vOka: Molecular and cellular biology of its skin attenuation - Cristina Tommasi; Andriani Drousioti; Judith Breuer (Human Vaccines & Immunotherapeutics)
Infection with varicella-zoster virus (VZV) causes chickenpox and shingles, both manifesting as a blistering skin rash. The skin is central to VZV, as the site of viral replication, transmission from cell-free virus in blisters and as the gateway to sensory nerves for establishing latency. The existing chickenpox vaccine is based on the live attenuated vOka strain and is impaired for replication in skin. While the genetics of the vOka vaccine have been extensively studied, critical gaps exist in understanding the molecular and cellular mechanisms of vOka attenuation, particularly in human skin models. This review aims to explore the molecular biology of vOka vaccine, focusing on its genetic diversity, interaction with host skin pathways, and the impact of vOka mutations in key VZV genes on attenuation mechanisms in human skin models. Insights from this review may guide the development of next-generation varicella vaccines and enhance the understanding of VZV pathogenesis.